2019
DOI: 10.1101/575449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ligand-independent role of ErbB3 in endocytic recycling

Abstract: Running title: Integral role of ErbB3 in the endocytic recycling machineryIntegral role of ErbB3 in the endocytic recycling machinery 2 Abstract Internalisation and trafficking of activated receptor tyrosine kinases (RTKs) determines duration and spatial distribution of growth factor signalling. Here we show that the ErbB3 receptor, frequently overexpressed in invasive cancers, acts in a ligand-independent manner to sort cargo such as b1 integrins and the transferrin receptor (TfR) for endocytic recycling brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…However, in this study, we did not observe clear colocalised signals of labelled TAIII and integrin b1 at the plasma membrane. It has been reported that abrogation of the recycling pathway impairs integrin internalisation and downregulation of migratory activity [29]. Taken together with our observation that labelled TAIII colocalised with integrin b1 in intracellular vesicles of cells treated with labelled TAIII after internalisation of integrin β1 was allowed, TAIII might disrupt the regulatory machineries for tra cking vesicles, thereby suppressing internalisation of cell surface cargoes.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, in this study, we did not observe clear colocalised signals of labelled TAIII and integrin b1 at the plasma membrane. It has been reported that abrogation of the recycling pathway impairs integrin internalisation and downregulation of migratory activity [29]. Taken together with our observation that labelled TAIII colocalised with integrin b1 in intracellular vesicles of cells treated with labelled TAIII after internalisation of integrin β1 was allowed, TAIII might disrupt the regulatory machineries for tra cking vesicles, thereby suppressing internalisation of cell surface cargoes.…”
Section: Discussionsupporting
confidence: 87%
“…More than two decades, numerous efforts were made to reveal the overall network of integrin tra cking and various membrane-associating proteins were found to be involved in integrin tra cking [29,57]. It would also be interesting to explore the molecular targets of TAIII, which might expand our knowledge of the regulatory machineries for cargo transport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations